The jump Abalakov. an analysis from the index of use of the arms in basketball players of Holguín (Revista científica Olimpia, 2026)
The physical yield is fundamental in the basketball, due to the demands that it implies its preparation and participation in sport competitions, where the sport acting of a baloncestista is determined, demonstrating the level that has reached through the practice. For that reason, the objective was to value some variables that characterize the jump Abalakov in the baloncestistas of the position defenses belonging to the team of basketball of first category the county of Holguín during the general stage. In this jump type it depends on many variables of control motor like coordination intramuscular, it forces muscular, high degrees of power and good execution technique. Many of the established tests to measure the capacity of the jump, lack specificity or they are not adjusted to the reality of the sport action that one wants to measure. This, made us to meditate and to realize that to improve the yield of the jump in the Basketball, they should be controlled the index of use of the arms. They were also they used statistical methods as the stocking, deviation and variation coefficient. Inside the results you could appreciate favorable changes as for the values of the analyzed index of a test to other, and they are arrived to conclusions and precise recommendations.
Keywords: Jump vertical circle; General stage; Basketball